NEW HERMITE-HADAMARD TYPE INEQUALITIES VIA CONFORMABLE FRACTIONAL INTEGRALS CONCERNING DIFFERENTIABLE RELATIVE SEMI-(r; m; h1; h2)-CONVEX MAPPINGS AND THEIR APPLICATIONS - Kashuri, Artion; Iqbal, Sajid (Matematichki Bilten, 2020)
In this article, we first presented a new identity via conformable fractional integrals. By applied the concept of relative semi-\((r;m,h_1,h_2)\)-convexity and the obtained identity as an auxiliary result, some new estimates with respect to the left hand side of the Hermite--Hadamard type inequalities via conformable fractional integrals are given. Also, some applications to special means and error estimates for the midpoint formula are provided as well.